ALTERNATIF PEMILIHAN LOKASI BANDARA DOMESTIK DI KABUPATEN LAMONGAN - Gadik Cahyanto; Zulkifli Lubis (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Lamongan regency is a regency in East Java province and enter the strategic area of development of Kertasusila Gate, Juanda Airport development discourse began to be raised to the surface. Was triggered by a prediction in 2019 which mentions Juanda International Airport experiencing passenger and flight density, coinciding with AFTA in 2015 which is an ASEAN Open Sky program held in ASEAN. East Java Provincial Government puts the plan into East Java Provincial RTRW 2011-2031. The airport development in Lamongan Regency has also been included in the document of East Java Province Transportation (Tatrawil) in 2012-2032. Therefore it is necessary to determine the location of the airport in Lamongan Regency. This Research In accordance with KM No. 20 Year 2014 Minister of Transportation on the procedures and procedures for determining the location of the airport then the feasibility of determining the location of the new airport is based on 2 aspects of feasibility in use to confirm the variables that affect the determination of alternative locations in Lamongan regency namely the administrative and technical aspects. Based on multi-criteria analysis then selected alternative location in Paciran village South axis on the left side of the direction from Gresik City to Tuban. Based on analysis and observation overlay obtained airport matching location is in Paciran district with coordinates 6º53'09.13 "S, 112º 22 ' 19.31 "T (Elevation 7m, eye height 5.75 km).